Mapping the use of extended reality (XR) in radiation oncology education: a scoping review protocol - Sze-Yuen Yau; Ching-Yi Lee; Hung-Yi Lai; Ching-Hsin Lee; Mi-Mi Chen; Po-Jui Chen (BMJ Open)
Introduction As the field of radiation oncology continues to evolve with rapidly advancing technologies, the need for innovative educational methods is critical. Extended reality (XR) technologies—including virtual reality, augmented reality and mixed reality—have emerged as transformative tools in medical education. While the potential of XR in healthcare education is recognised, there is a lack of comprehensive exploration specifically in the context of radiation oncology education. This scoping review aims to map the existing literature on XR technologies in radiation oncology training and education, identify barriers to their adoption and highlight opportunities for broader integration into curricula.Methods This scoping review will follow the Arksey and O'Malley framework with enhancements by Levac et al and will adhere to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines. A comprehensive search will be conducted across databases, including MEDLINE, Scopus and Web of Science, to identify relevant studies on the use of XR technologies in radiation oncology education. Studies will be selected based on predetermined inclusion criteria using the population, concept, context framework. Data extraction will focus on the types of XR technologies used, educational settings, learning outcomes, barriers to adoption and methodologies for evaluating XR effectiveness. The results will be synthesised through descriptive statistics and qualitative thematic analysis. A consultation phase will engage experts to refine findings and ensure the practical relevance of the review.Ethics and dissemination This protocol does not require ethics approval at the current stage as it involves a scoping review of publicly available literature. Ethics approval will be obtained prior to initiating the consultation phase involving experts. Written informed consent will be obtained from all individual participants included in the study. The study will be conducted in accordance with relevant guidelines and regulations and was approved by the Chang Gung Medical Foundation Institutional Review Board on 13 May 2025 (ref.: 202500731B0). The findings of this review will be disseminated through peer-reviewed publications, conference presentations and tailored executive summaries aimed at educators, policymakers and stakeholders in radiation oncology education.